Using high‐throughput sequencing in support of a plant health outbreak reveals novel viruses in Ullucus tuberosus (Basellaceae). (12th December 2018) - Fox, A.; Fowkes, A. R.; Skelton, A.; Harju, V.; Buxton‐Kirk, A.; Kelly, M.; Forde, S. M. D.; Pufal, H.; Conyers, C.; Ward, R.; Weekes, R.; Boonham, N.; et al.
Abstract : Ullucus tuberosus (ulluco) is a tuber‐forming species that has become a novel crop in highland and temperate maritime climates. Eight viruses have been previously reported infecting Ullucus, including Andean potato latent virus (APLV), a quarantine virus within the European Union. No reference sequences have been published for the viruses previously described from U .  tuberosus . Plants grown in the UK for the internet trade were tested for the presence of quarantine viruses using ELISA and real‐time RT‐PCR. ELISA positive results were obtained for APLV and multiple other viruses. A similar suite of viruses was detected at a second outbreak site linked to horticultural trade. Virus identification was by high‐throughput sequencing (HTS) using a ribosomal RNA (rRNA)‐depleted total RNA approach. Analysis of viral contigs indicated the presence of several novel viruses closely related to, but not consistent with, the viruses indicated by ELISA. Further confirmatory testing by real‐time RT‐PCR indicated that two tymoviruses, tentatively named Ullucus tymovirus 1 and Ullucus tymovirus 2, were more closely related to each other (85% identity), than to APLV or Andean potato mild mosaic virus (63–66% identity). APLV could not be confirmed from either site by either HTS or PCR. A novel tobamovirus (Ullucus tobamovirus 1) was only detected at the initial outbreak site. A novel polerovirus (Ullucus polerovirus 1) and a distinct genotype of Papaya mosaic virus were detected from both outbreak sites. Deploying HTS during a plant health outbreak demonstrates the potential of this approach to give rapid, accurate diagnosis.